2013
DOI: 10.1111/dme.12104
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the fatty liver index as an indicator of hepatic steatosis for predicting incident diabetes independently of insulin resistance in a Korean population

Abstract: Our results suggest that fatty liver index as a simple surrogate indicator of hepatic steatosis is valuable in identifying subjects at high risk for Type 2 diabetes. In addition, fatty liver disease itself contributes to the development of Type 2 diabetes independently of systemic insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 30 publications
0
35
1
1
Order By: Relevance
“…Anthropometric correlates for central obesity, fasting triglycerides and GGT levels are utilized in the fatty liver index commonly used in epidemiological studies, which along with its sex-specific derivative, the lipid accumulation product, accurately predicts the presence of hepatic steatosis, and could help clinicians identify patients at increased cardiometabolic risk eligible for further diagnostic evaluation and for whom suitable lifestyle-based interventions may be indicated [34][35][36][37] . Subsequently developed models such as the NAFLD liver fat score [38] substitute GGT for the AST/ALT ratio (AAR) in addition to incorporating clinical or biochemical markers of IR.…”
Section: Composite Diagnostic Models For Hepatic Steatosismentioning
confidence: 99%
“…Anthropometric correlates for central obesity, fasting triglycerides and GGT levels are utilized in the fatty liver index commonly used in epidemiological studies, which along with its sex-specific derivative, the lipid accumulation product, accurately predicts the presence of hepatic steatosis, and could help clinicians identify patients at increased cardiometabolic risk eligible for further diagnostic evaluation and for whom suitable lifestyle-based interventions may be indicated [34][35][36][37] . Subsequently developed models such as the NAFLD liver fat score [38] substitute GGT for the AST/ALT ratio (AAR) in addition to incorporating clinical or biochemical markers of IR.…”
Section: Composite Diagnostic Models For Hepatic Steatosismentioning
confidence: 99%
“…The National Health and Nutrition Survey reported that approximately 9.5 million people were strongly suspected as having DM, and a further 11.0 million people were possible candidates for having DM19. However, a previous study in Asian populations did not classify prediabetes among subjects without DM16. Previous studies in Japan did not include subjects with impaired glucose tolerance (IGT) and IFG9,10; but nevertheless, there were 20.5 million people at high risk of having diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that people with NAFLD are more than twice likely to have T2DM [7], and even moderate elevation in alanine aminotransferase (ALT) levels, a poor surrogate of fatty liver, was found to be associated with high-normal glucose levels [8]. Moreover, prospective studies suggest that people with NAFLD are more likely to have T2DM at all time points of follow-up [9], [10], [11], [12], [13]. Therefore, the available evidence suggests that the deposition of fat in the liver might play a role in the development of T2DM.…”
Section: Introductionmentioning
confidence: 99%